Factors Influencing Parent and Guardian Decisions on Vaccinating Their Children Against SARS-CoV-2: A Qualitative Study - Andrea Nickerson MS; Luis Gutierrez-Mock MA, MPH; Laura Buback MPH; Susie Welty MPH; Lynhea M. Anicete MS; Sabrina Sanchez MA; Wayne T.A. Enanoria PhD; Mike Reid MD (SAGE Publishing, 2023)
This qualitative analysis sought to explore factors that influenced parent/guardian intentions to vaccinate their children against SARS-CoV-2 in San Francisco, California, USA in order to inform San Francisco Department of Public Health's (SFDPH) youth vaccine rollout program. 30-minute, semi-structured telephone interviews were conducted with parents and guardians in either Spanish or English. Respondents shared their perspectives on vaccinating their children against SARS-CoV-2. Interviews were conducted over the telephone and recorded on Zoom. Participants (n = 40) were parents/guardians responding on behalf of their adolescent children (age 13+) and parents/guardians identified from the SFDPH COVID-19 testing database who tested for SARS-CoV-2 within the last 2 weeks. Interviews were conducted, audio recorded, transcribed, translated into English as appropriate, and rapidly analyzed in REDCap according to matrix analysis methodology to develop parent study themes. Perspectives on child vaccination were then explored through thematic analysis. Three themes were identified from the thematic analysis: (1) parental desires for children to return to school safely, (2) unclear messaging and information on COVID-19 prevention and vaccination, and (3) consideration of child's desires or opinions on receiving the vaccine. This study highlights specific factors influencing parent/guardian decisions on whether to vaccinate their children against SARS-CoV-2. The analysis also illustrates a potential role for children to play in influencing household vaccine decision-making.